The application of strength-based positive psychology program for elite archers - Youngsook Kim; Inchon Park (Korea Institute of Sport Science, 2020)
Purpose The goal of this study was to investigate the application effect of strength-based positive psychology intervention to elite archers. Methods Total of 20 elite archers participated in this study. Treatment group consisted of 10 elite archers participated in the strength-based positive psychology intervention for 8 weeks. Each individual responded the questionnaires in pre- and post-treatment sessions. Data were analyzed by repeated-measure ANOVA. Furthermore, archers participated in the program responded to in-depth interviews. Results According to the results, participants in strength-based positive psychology intervention showed that significantly increased strength knowledge, strength use, and optimism in the post-treatment compared to the pre-treatment session while control group did not show significant changes. In addition, archers perceived that there were positive effect on thinking ·coping and their self-confidence and self-esteem enhanced after participating the program. Conclusion The results of this study suggested that strength-based positive psychology intervention has positive impact on athlete's wellbeing and perception of individuals strength and can be applicable to different sports field.